Foucault et les sciences humaines, un rapport de biais : l’exemple de la sociologie du droit - Lascoume, Pierre (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1993)
This article expresses some ideas on the application of the methodological and epistemological principles, drawn from the concept of Michel Foucault, to legal sociology. In fact, Michel Foucault urged that his work be considered a tool-box where useful working instruments could be found. Among these, we find three types of instruments, conceptual, methodological and epistemological. This article discusses four epistemological principles taken from the work of Michel Foucault, namely (I) the break with anthro-pologism and with the cult of Man ; (2) rejection of the universals of thought; (3) the description of the paradigms for truth, understood as the conditions for true discourse, as defined in specific social formations ; (4) critical materialism. We also take into account a double principle of objectivication in the work of Foucault. The first of these principles acts at a more global level whereas the second operates analytically. We discuss how these epistemological principles and these objectivication forms guided us in our related sociological studies on the law. We also show how these studies were inspired by the work of Foucault, who, like De la gouvernementalité, were published after his death.